2020
DOI: 10.5334/dsj-2020-051
|View full text |Cite
|
Sign up to set email alerts
|

Historical Scientific Analog Data: Life Sciences Faculty’s Perspectives on Management, Reuse and Preservation

Abstract: Older data in paper or analog format (e.g., field/lab notebooks, photos, maps) held in labs, offices, and archives across research institutions are an often overlooked resource for potential reuse in new scientific studies. However, there are few mechanisms to help researchers find existing analog data in order to reuse it. Yet, in the literature, reuse of historical data is particularly important in studies of biodiversity and climate change.We surveyed life science researchers at the University of Minnesota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In an effort to get an idea of the scope of historic analog data held in offices and labs at one institution, an online survey of agricultural and life sciences researchers at the University of Minnesota was conducted, with 108 responses from 772 surveys sent out (Farrell et al, 2020). Questions focused on the nature of the data (topic, format, date range, amount, condition, perceived value) and whether it had been or might be reused.…”
Section: Projects Studying Historic Datamentioning
confidence: 99%
“…In an effort to get an idea of the scope of historic analog data held in offices and labs at one institution, an online survey of agricultural and life sciences researchers at the University of Minnesota was conducted, with 108 responses from 772 surveys sent out (Farrell et al, 2020). Questions focused on the nature of the data (topic, format, date range, amount, condition, perceived value) and whether it had been or might be reused.…”
Section: Projects Studying Historic Datamentioning
confidence: 99%
“…Many standards exist for doing this with digital data and those can be used for analog data as well. In a survey of those holding analog data, many reported that there was a person who could describe the origins of the data but fewer had documented that information (Farrell et al 2020). If you have used historic data, think about how you found it and how you wish you might have been able to find it.…”
Section: Possible Paths Forwardmentioning
confidence: 99%
“…Our interest in this topic began when a few senior faculty members approached the University library for assistance in organizing and possibly housing their analog data (Farrell et al 2019). A survey of life sciences researchers on campus revealed that many held analog data and considered it valuable but were unsure of how to preserve it (Farrell et al 2020). Nearly all were willing to share it.…”
Section: Introductionmentioning
confidence: 99%